Representasi Makna Rahmat Pada Lirik Lagu “Rahmatun Lil’alameen” Karya Maher Zain (Kajian Semiotika) - Rahim, Muhammad; Fikri; Hudri, Mawaddah (Al-Jawhar : Journal of Arabic Language, 2023)
This article aims to analyze meaning of mercy in the song “Rahmatul Lil’alameen” by Maher zain with the Roland Barthes’s semiotics theory. Barthes stated in his theory that meaning have three meanings namely, denotation, connotation and myth. Those meanings used to represent meaning of mercy that implied in the song. The research approach in this research uses a qualitative method approach. This approach used to represent and explain deeper about study of meaning as research object. Data collection using observation techniques. The researcher listened to the song carefully, then noted the words that had the meaning of grace. The data that has been recorded is then analyzed based on the semiotic theory of Roland Barthes. The research results show that the denotational meaning of the lyrics of the song "Rahmatun Lil'alameen" is the writer's concern for expressing love and respect for the Prophet and his teachings. The connotation of the song writer wants to remind you of the Prophet's teachings about love, kindness and compassion to obtain grace. The meaning of the myth, the creator of the song wants to convey that by carrying out and loving the Prophet you will be given grace and intercession which is important for every servant who wants salvation.